Exploring Islamic Social Environment's Role in English Proficiency: ‘‘Mondok’’ vs ‘‘Nyolok’’ Students - Sitti Surya Pramudita; Indah Werdiningsih; Anita Fatimatul Laeli (Universitas Islam Negeri Palopo, 2025)
This study examines English proficiency differences between Mondok (full-time Islamic boarding) and Nyolok (daily commuting) students in an Islamic vocational Pesantren in Jember, Indonesia. Using mixed-methods with 40 female students (20 each group), tests revealed Mondok students scored significantly higher (68.50 vs. 63.25; p = .038). Despite this 5.25-point difference, both groups achieved intermediate proficiency through distinct pathways—demonstrating Complex Dynamic Systems Theory's principle of equifinality. Qualitative data showed Mondok students, despite technological constraints, developed adaptive strategies like peer learning and utilized limited